Iridoids from the roots of Valeriana jatamansi Jones. (September 2017) - Wang, Ru-Jing; Chen, Hai-Mei; Yang, Fan; Deng, Yun; AO, Hui; Xie, Xiao-Fang; Li, Hong-Xiang; Zhang, Hai; Cao, Zhi-Xing; Zhu, Li-Xia; Chen, Yin; Peng, Cheng; et al.
Abstract: Five iridoids, named as chlorovaltrate P-T, together with six known analogues, (4 β, 8 β )-8-methoxy-3-methoxy-10-methylene-2, 9-dioxatricyclo[4.3.1.0 3, 7 ]decan-4-ol, chlorovaltrate A, (1 R, 3 R, 5 R, 7 S, 8 R, 9 S )-3, 8-epoxy-1- O -ethyl-5-hydroxyvalechlorine, 8-methoxy-4-acetoxy-3-chlormethyl-10-methylen-2, 9-dioxa-tricyclo[4.3.1.0 3, 7 ]decan, (1 S, 3 R, 5 R, 7 S, 8 R, 9 S )-3, 8-epoxy-1- O -ethyl-5-hydroxyvalechlorine, (1 R, 3 R, 5 R, 7 S, 8 R, 9 S )-3, 8-epoxy-1- O -methyl-5-hydroxyvalechlorine were isolated from the roots of Valeriana jatamansi (syn. Valeriana wallichii ). Their structures were elucidated by extensive analysis of 1D, 2D NMR and HRESIMS spectroscopic. The absolute configuration of chlorovaltrate P-T were established by comparing their experimental and calculated electronic circular dichroism (ECD) spectra. 3, 8-epoxy iridoids exhibited weak cytotoxicity against the lung adenocarcinoma (A 549) and gastric carcinoma cells (SGC 7901). Some also showed moderate neuroprotective effects against CoCl2 -induced neuronal cell death in PC12 cells. Graphical abstract: Highlights: Isolation of11 iridoids including5 previously undescribed compounds. A part of the isolates exhibited weak cytotoxicity against A549. A part of the compounds showed potent neuroprotective effects.